Syekh Abdul Karim Amrullah (Haji Rasul) dan Jaringan Keilmuan Ulama Melayu Lintas Selat Malaka (1879–1945) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This article examines Sheikh Abdul Karim Amrullah (Haji Rasul) (1879–1945) as an important figure in the network of Malay scholars across the Malacca Strait from the late 19th century to the mid-20th century. This study begins with the question: how did patterns of mobility, transmission of scholarly authority, and circulation of ideas of Islamic renewal connect Minangkabau–East Coast Sumatra with centers of learning in the Malay Peninsula? The method used is qualitative research based on literature study with an intellectual-historical approach and conceptual network analysis, through tracing works, correspondence, travel notes, and documentation of educational institutions and religious media during the relevant period. The findings show that Haji Rasul combined three paths of authority formation: the tradition of local surau and pengajian, his learning experience in the Haramain, and the articulation of ideas through madrasahs, magazines, and public debates. Through students, intellectual families, and publishing networks, ideas about tajdid, educational rationalization, and socio-religious ethics moved dynamically across the Malacca Strait, forming a shared discursive space in the Malay world. This study concludes that this scientific network was not merely a teacher-student relationship, but rather an ecosystem of knowledge production that brought together mobility, institutions, and media, and contributed to the transformation of modern Islam in the region.